Impacts of Audit Indepedence on Financial Performance of an Organization, a Case Study KARLO Embu - Githinji, Mary Muthoni (University of Embu, 2019)
This research was carried out in order to examine the impact of audit independence on financial performance in KARLO EMBU. To determine the relationship between audit independence and financial performance of KARLO in Embu. To examine the existing interaction between the audit independence and quality of financial report and to determine which form of auditing is mostly preferred in KARLO EMBU. Hence, the study is a movement towards improving the quality of audit practice. In conducting this research both primary and secondary data were used. The study captured the opinions of respondents who included 20 workers from the institutions which were analyzed using the SPSS software. The data gathered were used to test the research hypotheses and answer some of the research questions. The study found a significant and positive relationship between audit quality and the quality of financial performance